The analysis of psychometric properties of Human Figure Drawings’ Test - Nasvytienė, Dalia (Psichologija, 2007)
The present study investigated whether Human Figure Drawings (HFD) can be considered as valid and reliable devices to assess intellectual abilities as well as the emotional adjustment in the practice of child psychologists. HFD are most popular of all drawing techniques often included in test batteries as relatively short, easy-to-administer, friendly and non-threatening measures. Contradictory empirical evidence concerning their psychometric properties is presented with the aim to overcome the gap between large scale of practical use and a relatively small amount of scientific investigations. Draw-A-Person: A Quantitative Scoring System (DAP: QSS) and Draw-A-Person: Screening Procedure for Emotional Disturbance (DAP: SPED) created by Naglieri J. and colleagues were chosen as the most modern and objective scoring systems in regard to other HFD. Both techniques and WISC-IIILT were administered to a clinical sample consisting of 95 children aged 6–16 with emotional/behavioural disturbances and 70 children without clinical disturbances closely matched for the age and gender criteria. T-test, correlations, discriminant and exploratory factor analysis were applied for data analysis. Results suggest that DAP:QSS shortly meets standards of concurrent validity with WISC-IIILT as it was found no statistically significant correlations with the scores of Wechsler Intelligence Scale for Children-IIILT (p > 0.05). A additionally, noncognitive factors – liking to draw and clinical disturbance – can cause biased results of the assessment of intellectual abilities when using DAP: QSS: liking to draw correlates with the higher results as compared to WISC-IIILT scores, while intellectual abilities of the children with clinical disturbance were underestimated (p = 0.00). Standard error of estimation appeared to be higher when using DAP: QSS than WISC-IIILT. The total score of Draw-A-Person:Screening Procedure for Emotional Disturbance was significantly higher in the clinical sample (p = 0.00). It proves the validity of this instrument to screen the children for emotional maladjustment but the cases of false-negative screening cast doubt about its strength. Both devices showed good reliability (internal consistency as well as inter-scorer).
Keywords: Human Figure drawing; reliability; validity; children / adolescent psychological assessment